2007
DOI: 10.1002/jcb.21348
|View full text |Cite
|
Sign up to set email alerts
|

Delayed activation of PKCδ and NFκB and higher radioprotection in splenic lymphocytes by copper (II)–Curcumin (1:1) complex as compared to curcumin

Abstract: A mononuclear 1:1 copper complex of curcumin had been found to be superior to curcumin in its anti-oxidant properties. This paper describes the radio-protective effects of the complex in splenic lymphocytes from swiss mice. The complex was found to be very effective in protecting the cells against radiation-induced suppression of glutathione peroxidase, catalase and superoxide dismutase (SOD) activities. Both curcumin and the complex protected radiation-induced protein carbonylation and lipid peroxidation in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…It can form complexes with metal ions e.g. cupuric [21] ion due to the presence of the ortho methoxy, phenolic and diketo groups in the molecule, which has been proposed to be one of the possible mechanisms for its instability when it is added to the solutions containing metal ions like PBS, cell medium, and plasma. Also, curcumin contains two active double bonds, which are active towards nucleophilic functional groups e.g.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…It can form complexes with metal ions e.g. cupuric [21] ion due to the presence of the ortho methoxy, phenolic and diketo groups in the molecule, which has been proposed to be one of the possible mechanisms for its instability when it is added to the solutions containing metal ions like PBS, cell medium, and plasma. Also, curcumin contains two active double bonds, which are active towards nucleophilic functional groups e.g.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…It seems that both ODC and NF-κB simultaneously exhibit a capacity for chemoresistance. Moreover, curcumin inhibits PKC δ activity and its downstream signaling pathway, transcription factor AP-1 (Balasubramanian and Eckert, 2007;Kunwar et al, 2007). The PKC δ inhibitor, rottlerin, represses ODC activity induced by prolactin in HL-60 cells and stimulates apoptosis of hematopoietic cell lines (Hsu et al, 2006;.…”
Section: Discussionmentioning
confidence: 99%
“…IκBα after degradation is known to release NF-κB, which acts in the nucleus as a transcription factor for many anti-apoptotic genes, thus indicating that the cell could be entering into a cytoprotective pathway. In this study, pretreatment of irradiated cells with curcumin-copper complex was shown to be effective in avoiding radiation-induced damage in these cells [60]. …”
Section: Effect Of Mitochondrial Ros Generation On Pkc Activitymentioning
confidence: 99%